The role of empagliflozin in the management of type 2 diabetes by patient profile - Hedrington MS; Davis SN (Dove Medical Press, 2015)
Maka S Hedrington, Stephen N Davis Department of Medicine, University of Maryland School of Medicine, Baltimore, MD, USA Abstract: Current recommendations for the management of type 2 diabetes mellitus (T2DM) include patient-centered approach, ie, targeting glycemic control based on patient and disease characteristics. Ten different classes of oral and injectable anti-hyperglycemic agents have been developed for T2DM, including the newest class – sodium–glucose cotransporter 2 (SGLT2) inhibitors. Four members of the class with comparable glycemic efficacy and side effects have gained approval in the US and the rest of the world. This review covers empagliflozin – third approved SGLT2 inhibitor in the US. The drug has shown rapid absorption reaching peak levels in ~2 hours and an elimination half-life of ~13 hours. Empagliflozin is a highly selective SGLT2 inhibitor with 2600-fold higher affinity for SGLT2 compared with SGLT1. Oral administration results in a dose-dependent inhibition of the transporters with increased urinary glucose excretion and resultant reduction in plasma glucose. Its efficacy and safety have been shown in a number of studies conducted in many countries. Across the trials, significant improvements in primary and secondary efficacy end points have been demonstrated, including reductions in HbA1c (~-0.8%), fasting plasma glucose (~-2 mmol/L), body weight (~-2 kg), and blood pressure (systolic -4 mmHg and diastolic -2 mmHg). Similar to other SGLT2 inhibitors, empagliflozin does not increase the risk for hypoglycemia, and the most commonly reported side effects are urinary and genital tract infections. Although empagliflozin can be used as the first-line monotherapy, its current place in the treatment of T2DM appears to be as an add-on to other oral anti-hyperglycemic agent(s) or insulin at any stage of the disease. Keywords: anti-hyperglycemic agents, diabetes, glucose, SGLT2